2014
DOI: 10.1021/jp500821u
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Study of Molecular Response of Amine Bases in Organic Solvents

Abstract: Reorientational correlation times of various amine bases (namely, pyridine, 2,6-lutidine, 2,2,6,6-tetramethylpiperidine) and organic solvents (dichloromethane, toluene) were determined by solution-state NMR relaxation time measurements and compared with predictions from molecular dynamics (MD) simulations. The amine bases are reagents in complex reactions catalyzed by frustrated Lewis pairs (FLP), which display remarkable activity in metal-free H2 scission. The comparison of measured and simulated correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…It is shown that: i) the onset of H 2 activation is at much larger boron···phosphorus distances than previously thought; ii) the system evolves to the product in a roaming-like fashion because of quasi-periodic nuclear motion along the asymmetric normal mode of P···HÀH···B fragment; iii) transient configurations of a certain type are present despite structural interference from the solvent; iv) transient-state configurations with sub-picosecond lifetime have potentially interesting infrared activity in the organic solvent (toluene) as well as in the gas phase. [9][10][11][12][13] Recently, we found the first-but already convincing-indications that the FLP activity in [1] has fundamental characteristics that are not captured in the transition-state/minimum-energy-pathway (TS/MEP) description. [1, 2] The two central aspects of [1] are that: i) the dative adduct between bulky LB and LA species is not formed for steric reasons, hence the term (intermolecular) "frustrated" Lewis pairs (FLPs); ii) the encounter van der Waals (vdW) complexes between LB and LA species have not been unambiguously confirmed neither by experiment nor by theory.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown that: i) the onset of H 2 activation is at much larger boron···phosphorus distances than previously thought; ii) the system evolves to the product in a roaming-like fashion because of quasi-periodic nuclear motion along the asymmetric normal mode of P···HÀH···B fragment; iii) transient configurations of a certain type are present despite structural interference from the solvent; iv) transient-state configurations with sub-picosecond lifetime have potentially interesting infrared activity in the organic solvent (toluene) as well as in the gas phase. [9][10][11][12][13] Recently, we found the first-but already convincing-indications that the FLP activity in [1] has fundamental characteristics that are not captured in the transition-state/minimum-energy-pathway (TS/MEP) description. [1, 2] The two central aspects of [1] are that: i) the dative adduct between bulky LB and LA species is not formed for steric reasons, hence the term (intermolecular) "frustrated" Lewis pairs (FLPs); ii) the encounter van der Waals (vdW) complexes between LB and LA species have not been unambiguously confirmed neither by experiment nor by theory.…”
mentioning
confidence: 99%
“…[2] Despite considerable efforts, theoretical analyses of FLP activity carried out without applying a molecular dynamics methodology have not led to consensus with regard to the mechanism of [1]. [9][10][11][12][13] Recently, we found the first-but already convincing-indications that the FLP activity in [1] has fundamental characteristics that are not captured in the transition-state/minimum-energy-pathway (TS/MEP) description. [9][10][11][12][13] Recently, we found the first-but already convincing-indications that the FLP activity in [1] has fundamental characteristics that are not captured in the transition-state/minimum-energy-pathway (TS/MEP) description.…”
mentioning
confidence: 99%
“…[36] Further insights into the behaviour of some amine/BCF solutions were obtained by Autrey and Kathmann, who assessed the role of the structure of the amine in the strength of LA/LB interactions by means of NMR spectroscopy and calorimetric experiments. [37,38] In particular, 11 B NMR spectra of 5/BCF mixtures were reported to be identical to that of pure borane, in analogy to what is observed with 3 and 4 phosphines. This would mean that NH···F hydrogen bonding interactions do not favour the formation of dative adducts, at least in appreciable amounts.…”
Section: Intermolecular Flpsmentioning
confidence: 55%
“…This has been also confirmed by a 14 N NMR study, which indicated that chemical shift and relaxation constants of 5 are not affected by the presence of an equimolar amount of BCF. [38] Accordingly, no heat release was observed when the solution was formed, besides independent heats of dilution. On the other hand, for less encumbered bases, such as pyridine, forming only classical Lewis adducts with BCF, calorimetric experiments evidenced a heat release related to the formation of dative NÀB bonds, having a DG8 = À17 kcal mol…”
Section: Intermolecular Flpsmentioning
confidence: 99%
See 1 more Smart Citation